Effect of Insertion Time on Yield Of Edamame Soybean in Renek Cassava Intercropping - Mulyono; Marka, Difa Nabila; Astuti, Agung (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Overlapping is one way to optimize agricultural land. Apart from commodities, what needs to be considered in the intercropping system is the planting time. In this study, a combination of legume and non-legume plants had a shorter lifespan compared to other types, namely Edamame soybeans and Renek cassava. In this combination of plants, it is necessary to determine the right planting time at one time of planting. The purpose of this study was to determine the most appropriate insertion time for Edamame soybeans for Edamame soybean yields and to examine the potential utilization of land in the intercropping system of Edamame soybeans with Renek cassava arrangement consisting of four treatments, namely Edamame soybean monoculture, Edamame Soybeans were inserted into Renek cassava aged 0 Days After Planting (HST), 2 Weeks After Planting (MST), and 4 MST. In each treatment there were 3 replications, 3 sample plants, and 4 sacrificial plants. Parameters observed were number of leaves, plant dry weight, Edamame soybean yield, and Land Equivalence Value. data were analyzed using analysis of variance with a of 5% and then continued with duncan's multiple range test (DMRT) if significantly different. the results showed that there was a significant effect on the yield of Edamame soybean area per unit area. and it was found that the best treatment eas Edamame was Edamame soybeab which was inserted into renek cassava aged 2 MST which produced pods per unit area of 9.73 ton/ha with an NKL of 1.85.